2000
DOI: 10.1097/00007632-200007010-00012
|View full text |Cite
|
Sign up to set email alerts
|

A Noninvasive Anthropometric Technique for Measuring Kyphosis and Lordosis

Abstract: The proposed technique appears to give more representative results than those presented in the literature. It has the advantage of being part of a global noninvasive postural evaluation. Using this approach in a systematic manner could help reduce radiograph exposure while keeping track of the spine sagittal curvatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
2
20

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(82 citation statements)
references
References 25 publications
3
56
2
20
Order By: Relevance
“…The standing postures were thought to yield more comparable data. The 33°mean standing thoracic kyphosis with standard deviation (SD 11°) and 35°mean standing lordosis (SD 11.9°) measures obtained by the spinal wheel in this study are comparable with the 33°-36°kyphosis and the 28°-32°lordosis measures in previous studies [33,[56][57][58][59]. Ng et al [17] demonstrated lower values of lumbar lordosis (24°-28°) which could be related to measuring only male subjects with arguably less pronounced standing lordosis [17].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The standing postures were thought to yield more comparable data. The 33°mean standing thoracic kyphosis with standard deviation (SD 11°) and 35°mean standing lordosis (SD 11.9°) measures obtained by the spinal wheel in this study are comparable with the 33°-36°kyphosis and the 28°-32°lordosis measures in previous studies [33,[56][57][58][59]. Ng et al [17] demonstrated lower values of lumbar lordosis (24°-28°) which could be related to measuring only male subjects with arguably less pronounced standing lordosis [17].…”
Section: Discussionsupporting
confidence: 82%
“…Thoracic curvature measures demonstrated consistently better intra-, inter-and test-retest reliability compared to lumbar curvature measures with the highest errors in sitting lumbar curvatures. This observation was also made by Leroux et al [58] who reported ICC of 0.94 for kyphosis and 0.91 for lordosis with errors of 5°and 6°, respectively, when comparing radiographic and non-invasive stereographic techniques [58]. Relatively large lumbar spine movement in sagittal plane, with rather small contributions from rather more rigid thoracic region [64], could be associated with larger measurement error as measurement errors tend to increase with increased magnitude of the measured variable [65].…”
Section: Discussionsupporting
confidence: 54%
“…Leroux and Zabijek compared measurements of thoracic kyphosis; analysis of the results showed high correlation between the above methods. In the case of thoracic kyphosis the correlation coefficient was 0.89, while for lumbar lordosis it was slightly lower, at the level of 0.84 [29]. Saad et al found high compatibility and repeatability of results in studies comparing values of Cobb angle, measured with photogrammetric technique and in X-ray examination [19,30].…”
Section: Discussionmentioning
confidence: 99%
“…In some of the mentioned studies 3,7,8 , the methods for evaluating the pelvic tilt angle was indirect, and recent studies [9][10][11] , even though they did not show any specific data on pelvic positioning, have demonstrated that the determination of the balanced position of some body segments, indirectly measured through observations, had acceptable correlations with radiographic imaging. In these studies [9][10][11] , individuals were observed using photographs taken at several moments with skin markers positioned over certain bone prominences.…”
Section: Introductionmentioning
confidence: 99%
“…In these studies [9][10][11] , individuals were observed using photographs taken at several moments with skin markers positioned over certain bone prominences. Sacco et al 12 used software for posture assessment called Software para Avaliação Postural (SAPO), that is distributed for free and was designed by Brazilian researchers aiming to assist health care professionals in evaluating posture.…”
Section: Introductionmentioning
confidence: 99%